Learn Xcode Tools for Mac OS X and iPhone Development - Piper, Ian (Apress, 2012)
Apple’s products have always had the reputation (richly deserved in my opinion) of providing the easiest to learn and richest working environment of any computer system. As Mac or iPhone users we are privileged: software that requires little time, effort, or documentation to become productive is the rule rather than the exception. Unfortunately, that rule hasn’t historically extended to the tools and technologies used to create such programs. Learning to write software for the Mac has traditionally involved a major investment of intellectual effort and time in new tools, technologies, and techniques. I have thought for a long time that this is an essentially artificial barrier. Delivery in the sophisticated environment of the Mac and iPhone takes a lot of effort behind the scenes, and there is no doubt that learning to write software that works in such environments involves taking on a significant burden of new technologies and concepts. However, I believe that, with suitably accessible tools, and some good, clear, written guidance, creating great Mac and iPhone software should be within the grasp of most competent developers. With the latest release of the Xcode Developer Tools, the new developer has access to a formidable tool-chest for Mac and iPhone development that is easier to use than any previous version. The missing piece, to me, has always been a simple and clear description of the tools and technologies needed to write for the Mac and iPhone. That is why I have written this book.